Etos Kerja Dalam Al-Qur’an - Helmy Syamsuri, Abdul Sumarlin; Muhammad Yusuf, Ahmad Mujahid (Economics and Digital Business Review, 2024)
This research aims to find out about the concept of work ethic in the Al-Qur'an. The work ethic in the Qur'an is an Islamic view of the importance of doing work as a form of worship to Allah SWT. This research uses the library research method or literature review with data collection carried out in several stages, starting from collecting references to analyzing references that are relevant to this research. The data sources are obtained from literature reviews from books, journals, the internet and other media. The results of the analysis in this research show that the work ethic in the study of the Qur'an is found in the Word of Allah, and shows that every Muslim is expected to be able and have a work ethic that is in accordance with the instructions of the Qur'an and hadith so that they become professional human beings. reliable and effective for everyone. In working, every Muslim is obliged to have a foundation of trust and sincerity, and try as hard as possible with the principles of doing the best, being trustworthy and steadfast and hoping for the blessing of Allah SWT.